THE ROLE OF INNOVATIVE TENDENCIES IN THE FIGHT AGAINST CORRUPTION IN THE HIGHER EDUCATION SYSTEM - Rasulova Gulbakhor Abidjanovna (Scholar Express Journals, 2023)
In the article, higher education institutions specializing in the field of economics, law, and information technologies, as well as faculties (majors) specializing in the field of economics, law, and information technologies, in the higher education institutions, by introducing a system of paid services, increase its income and, as a result, provide employees in the field with an adequate salary to reduce corrupt situations in their activities by providing Also, specific scientifically based suggestions on the expected results are given
Keywords: corruption; financial independence; outsourcing; services